Dose-response of weanling pigs to streptococcus faecium - Healy, B.J.; Hancock, Joe D.; Fung, Daniel Y. C.; Liang, C.; Yu, S.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two 5-wk experiments, using a total of 270 pigs (avg initial wt of 16.1 and 13.11b), were conducted to determine the dose-response relationship between Streptococcus faecium additions to drinking water and performance of newly weaned pigs. In experiment 1, treatments were: 1) untreated control; 2, 3, and 4) .5, 2.5, and 4.5 x 109 CFU of S. faecillm/pig/d; 5) antibioticfed positive control (CSP250 and CUS04)' Bacterial content of feces collected from the pigs on d 7, 14, and 21 indicated that antibiotic feeding greatly reduced fecal content of streptococci. S. faecium given in the water (.5, 2.5, or 4.5 x 10 CFU/pig/d) slightly increased the CFU of streptococci in the feces. Giving S. faecillm in the water or antibiotics in the feed did not reduce fecal content of coliform bacteria. Antibiotic feeding improved feed intake, growth rate, and efficiency of gain when compared to the untreated control. Pigs given the highest level of S. faecium addition to the water (i.e., 4.5 x 10^9 had performance that was intermediate to that of the untreated control and positive control. In experiment 2, dosages of S. faecium were spread further apart. Treatments were: 1) untreated negative control; 2,3, and 4) 5 x 107, 5 X 109, and 5 x 1011 CFU of S. faecium/pig/d; and 5) antibiotic-fed positive control. Streptococci content of the feces was increased by giving S. faecillm in the water. However, total coliform content was not affected by giving S. faecium or antibiotics. Antibiotic feeding improved rate of gain, feed intake, and efficiency of gain, but giving S. faecium did not improve performance of pigs compared to those given the untreated control.
Keywords: Swine; Streptococcus faecium; Probiotics; Antibiotics; Performance; Weanling pig